RNA m6A-mediated post-transcriptional repression of glucocorticoid receptor in LPS-activated Kupffer cells on broilers - Yulan Zhao; Yidan Jiang; Yue Feng; Ruqian Zhao (Poultry Science)
Glucocorticoid receptors are distributed in various cells of the body and participate in the regulation of metabolism and immunity in response to glucocorticoids. RNA m6A methylation participates in various metabolic and inflammatory responses, yet it remains elusive whether m6A is involved in GR regulation during immune activation. Here, we observed uncoupled GR responses with increased mRNA yet suppressed protein levels in the LPS-challenged broilers chicken liver, in association with global elevation of RNA m6A methylation, especially in the expression of METTL3 and YTHDF2. Further analysis using isolated primary hepatocytes and Kupffer cells revealed that such uncoupled GR responses and m6A hypermethylation occurred specifically in KCs. The same GR and m6A responses were reproduced in LPS-activated KC cell line, implying a possible role of m6A in the post-transcriptional suppression of GR in KC. Indeed, m6A inhibitor cycloleucine alleviated LPS-induced GR protein suppression, whilst GR antagonist RU486 had no effect on global m6A methylation in KC. We observed that YTHDF2 siRNA can alleviate LPS-induced GR mRNA stability decrease. Subsequently, specific m6A sites on GR were predicted and verified. Mutation m6A sites and luciferase reporter assay was also applied to validate these findings. Mechanistically, m6A methylation on the transcripts of GR impairs its mRNA stability in a YTHDF2-dependent manner, which leads to the decrease of its protein. Our study indicates successive roles of RNA m6A modification in the down regulation of GR expression, which provides new drug targets for epigenetic therapy of liver inflammation.